1982
DOI: 10.1111/j.1365-2923.1982.tb01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and performance in psychiatric education

Abstract: An attempt was made in this study to develop a composite profile of personality characteristics of medical students that correlated differentially with successful achievement outcomes in the Psychiatry CLerkship at a University of Toronto teaching hospital. Data on 27 of 33 final year medical students in a psychiatry rotation programme were used to analyse canonical correlations between personality and achievement variables. The findings of the study indicated that success in clinical examinations was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Studies have found various personality questionnaires useful (Cattell et al 1970; Pollock et al 1982; Reeve & Watson 1985) as well as unhelpful (Green et al 1991) for identifying personality variables in relation to the selection of candidates, performance and career choice in the medical profession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found various personality questionnaires useful (Cattell et al 1970; Pollock et al 1982; Reeve & Watson 1985) as well as unhelpful (Green et al 1991) for identifying personality variables in relation to the selection of candidates, performance and career choice in the medical profession.…”
Section: Introductionmentioning
confidence: 99%
“…
al. 1982;Aldrich 1987;Weiss et al 1988) the value of per-This study deals with personality variables of medical students in relation to their academic success in the preclinical stage.
…”
mentioning
confidence: 99%
“…In an attempt to improve on such subjective judgements, a variety of personality tests have been used. These have also shown conflicting results: some studies have indicated a predictive value, particularly in relation to clinical competence (Pollock et al 1982), others have not (Aldrich 1987; Weiss et al 1988). A recent retrospective survey of medical students sitting their final MB BCh examination was undertaken and no relationship was found between personality and academic performance throughout the course (Green et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of personality tests have been used over the years in different parts of the world. Although some have been shown to have a value particularly in the prediction of clinical competence (Pollock et al 1982) others have not (Aldrich 1987; Weiss et al 1988).…”
Section: Introductionmentioning
confidence: 99%